Design and Realization of a Novel Optically Disordered Material: A Demonstration of a Mie Glass. Issue 10 (6th April 2017) - Miranda‐Muñoz, José M.; Lozano, Gabriel; Míguez, Hernán
Abstract : Herein, a diffusive material presenting optical disorder is introduced, which represents an example of a Mie glass. Comprising spherical crystalline TiO2 nanoparticles randomly dispersed in a mesoporous TiO2 matrix, it is proved that the scattering of light in this inhomogeneous solid can be predicted in an unprecedented manner from single‐particle considerations employing Mie theory. To that aim, a study of the dependence of the key parameters employed is performed to describe light propagation in random media, i.e., the scattering mean free path and the transport mean free path, as a function of the size and concentration of the spherical inclusions based on a comparison between experimental results and analytical calculations. It is also demonstrated that Mie glasses enable enhanced fluorescence intensity due to a combined absorptance enhancement of the excitation light combined with an improved outcoupling of the emitted light. The method offers the possibility to perform a deterministic design for the realization of a light diffuser with tailor‐made scattering properties. Abstract : Mie glasses are inhomogeneous solids that behave as solid dispersions of light scatterers. A full optical characterization of this material is performed to attain the key parameters that describe light propagation in random media. The potential of Mie glasses for color conversion is confirmed by sensitizing them with fluorescent dyes, resulting in spontaneous emission enhancement.